Synthesis of Main-Chain Poly(fullerene)s from a Sterically Controlled Azomethine Ylide Cycloaddition Polymerization - Ramanitra, Hasina H.; Santos Silva, Hugo; Bregadiolli, Bruna A. [UNESP]; Khoukh, Abdel; Combe, Craig M. S.; Dowland, Simon A.; Bégué, Didier; Graeff, Carlos F. O. [UNESP]; Dagron-Lartigau, Christine; Distler, Andreas; Morse, Graham; Hiorns, Roger C. (American Chemical Society (ACS), 2016)
Fullerene is used as a monomer in this simple method to prepare soluble, well-defined polymers. The sterically controlled azomethine ylide cycloaddition polymerization of fullerene (SACAP) yields macromolecules with molecular weights of around 25 000 g mol-1. Importantly, cumbersome comonomers are employed to restrict cross-linking. Extensive characterizations, with the help of modeling studies, indicate that the polymers are regio-irregular with a majority of trans-3 isomers. Of particular interest is the exceptional ease of preparing polymers with zero metal content.